u(x) = (x²+1) sin x f = x² +1 --> f' = 2x g = sin x --> g' = cos x u' = f' g + f g' = 2x sin x + (x²+1) cos x
y = u³ y' = 3 u². u'
y' = 3 { (x²+1) sin (x)}².{ 2x sin x + (x² + 1) cos x ) y' = 3 (x²+1)² sin² x [ 2x sin x + (x² +1) cos x ] y' = 6x (x²+1)² sin³ x + 3(x²+1)³ sin² x cos x
Verified answer
TurunaN Fungsi MaJemuKy = {(x²+1) sin x} ³
u(x) = (x²+1) sin x
f = x² +1 --> f' = 2x
g = sin x --> g' = cos x
u' = f' g + f g' = 2x sin x + (x²+1) cos x
y = u³
y' = 3 u². u'
y' = 3 { (x²+1) sin (x)}².{ 2x sin x + (x² + 1) cos x )
y' = 3 (x²+1)² sin² x [ 2x sin x + (x² +1) cos x ]
y' = 6x (x²+1)² sin³ x + 3(x²+1)³ sin² x cos x